2003
DOI: 10.1128/aac.47.3.972-978.2003
|View full text |Cite
|
Sign up to set email alerts
|

Efflux-Mediated Resistance to Tigecycline (GAR-936) in Pseudomonas aeruginosa PAO1

Abstract: Pseudomonas aeruginosa strains are less susceptible to tigecycline (previously GAR-936; MIC, 8 g/ml) than many other bacteria (P. J. Petersen, N. V. Jacobus, W. J. Weiss, P. E. Sum, and R. T. Testa, Antimicrob. Agents Chemother. 43:738-744, 1999). To elucidate the mechanism of resistance to tigecycline, P. aeruginosa PAO1 strains defective in the MexAB-OprM and/or MexXY (OprM) efflux pumps were tested for susceptibility to tigecycline. Increased susceptibility to tigecycline (MIC, 0.5 to 1 g/ml) was specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
165
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(177 citation statements)
references
References 43 publications
8
165
0
4
Order By: Relevance
“…It is unlikely that this inhibition is due to disruption of ⌬pH by tigecycline because tigecycline did not significantly affect the formation of the proton motive force in the membrane vesicle study, as already described for the quinacrine fluorescence assay. These results are in good agreement with those in a recent paper by Dean et al (6), who reported the tigecycline resistance conferred by MexXY and possibly MexAB, which are Pseudomonas homologues of AcrAB.…”
Section: Induction Of Tet(b) By Tigecycline In E Coli W3104/plgt2 [Tsupporting
confidence: 83%
See 1 more Smart Citation
“…It is unlikely that this inhibition is due to disruption of ⌬pH by tigecycline because tigecycline did not significantly affect the formation of the proton motive force in the membrane vesicle study, as already described for the quinacrine fluorescence assay. These results are in good agreement with those in a recent paper by Dean et al (6), who reported the tigecycline resistance conferred by MexXY and possibly MexAB, which are Pseudomonas homologues of AcrAB.…”
Section: Induction Of Tet(b) By Tigecycline In E Coli W3104/plgt2 [Tsupporting
confidence: 83%
“…Tigecycline is a broadspectrum glycylcycline derivative (2) and is efficacious against highly resistant bacteria (1), including methicillin-resistant Staphylococcus aureus and penicillin-resistant Streptococcus pneumoniae. However, it is less active against clinically problematic opportunistic pathogens, such as Pseudomonas aeruginosa (6) and Proteus mirabilis (3,28).…”
mentioning
confidence: 99%
“…It is effective against many Gram-positive and Gram-negative microorganisms but has little activity against the non-fermenting CF pathogens P. aeruginosa and Burkholderia spp. The mechanism of resistance has been clearly demonstrated for P. aeruginosa, but in BCC it remains to be determined [4,10]. The data presented here indicate a role for efflux pumps.…”
Section: Discussionmentioning
confidence: 67%
“…A c c e p t e d M a n u s c r i p t 4 The aim of this study was to determine whether tigecycline resistance in BCC is medicated by efflux pumps and, if so, whether EPIs can be used to augment the efficacy of the glycylcycline molecule.…”
Section: Page 4 Of 15mentioning
confidence: 99%
See 1 more Smart Citation